A multi-tone high efficient bandwidth system with an eliminated even-order distortions using double dual-parallel Mach-Zehnder modulator - Taimur N. Mirza (Elsevier, 2021)
In this paper, a linearization of dual RF channels over a single carrier wavelength is proposed and experimentally demonstrated. Multiple microwave signals with a multi-octave bandwidth are modulated by a double dual-parallel Mach-Zehnder modulator (D-DPMZM) and recovered by a differential balanced detector (BPD). The theoretical and experimental model illustrates the elimination of second-order harmonic distortions (SHD) and second-order intermodulation (IMD2), and significant suppression of the third-order intermodulation (IMD3) by controlling the phase of the input RF signal and DPMZM. The proposed photonic link configuration illustrates the modulation of two microwave signals on a single optical carrier wavelength, and each RF channel is tested for Two-tone signals to illustrate the linearization of the channelized analog photonic link (CAPL). Firstly, a mathematical model is presented to illustrate the elimination of optical carrier and even-order distortions by using only single-tone in each RF channel. Secondly, the purity of the system is mathematically and experimentally investigated by introducing two-tones in each RF channel. We have analyzed both test cases, with single-tone and with a two-tone test, to help us understand and compare the performance of the system. For test case 1 and test case 2 of our proposed configuration, we have achieved a fundamental signal-to-interference ratio (S/I) of 60 dB and 65 dB with a spurious-free dynamic range (SFDR) of 110 dB.Hz2/3 and 116 dB.Hz2/3, respectively.